2018
DOI: 10.1007/s10802-018-0404-z
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Family Processes in Different Subgroups of Youth with Autism Spectrum Disorder

Abstract: We compared the maternal reports on mothering and family processes between 160 youth with autism spectrum disorder (ASD) and 160 age and gender-matched typically developing (TD) youth stratified by personal characteristics from Taiwan. The ASD groups consisted of 51 'typical autism' (TA), 52 'high-functioning autism' (HFA), and 57 'Asperger syndrome (AS).' Maternal reports showed that youth with ASD obtained less affection and more protection from the mother, and had less active mother-child interactions and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 107 publications
0
11
0
Order By: Relevance
“…We also assessed the moderation effects of family function and academic performance. We predicted that these factors were moderators because family and school environments are two crucial settings for the social development of school-aged children [Stevenson & Baker, 1987;Wagner, Silverman, & Martin, 2003] and are related to the functions of children with autistic traits [Chang et al, 2019;Chiang & Gau, 2016]. Overall, we tested the following three hypotheses: (a) children with elevated autistic traits have higher risks of suicidal ideation, plans, and attempts; (b) the association between elevated autistic traits and increased risk of suicidality remains when symptoms of depression/anxiety are considered; and (c) adequate family function and academic performance help mitigate suicide risk in children with elevated autistic traits.…”
Section: Introductionmentioning
confidence: 99%
“…We also assessed the moderation effects of family function and academic performance. We predicted that these factors were moderators because family and school environments are two crucial settings for the social development of school-aged children [Stevenson & Baker, 1987;Wagner, Silverman, & Martin, 2003] and are related to the functions of children with autistic traits [Chang et al, 2019;Chiang & Gau, 2016]. Overall, we tested the following three hypotheses: (a) children with elevated autistic traits have higher risks of suicidal ideation, plans, and attempts; (b) the association between elevated autistic traits and increased risk of suicidality remains when symptoms of depression/anxiety are considered; and (c) adequate family function and academic performance help mitigate suicide risk in children with elevated autistic traits.…”
Section: Introductionmentioning
confidence: 99%
“…The parenting literature on ASD has shown an emerging trend that during the early stages of child rearing, the parenting behaviors of parents of children with ASD do not seem to be significantly different from the parenting behaviors of parents of typically developing children, parents of children with intellectual disabilities, and parents of children with language disorder (e.g., Rutgers et al 2007). However, among parents of youths with ASD aged 7 to 17 years old, more negative parenting (e.g., physical control, harsh parenting) and less positive parenting (e.g., parental warmth and sensitivity) have been found (Chang et al 2018; Riany et al 2017). Although these studies are from an Asian population that was culture-specific, one reason for the more negative parenting might be that the challenging behaviors of youth with ASD are more visible and therefore have a more explicit effect on parenting.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that Chinese mothers of children with ASD reported providing lower levels of maternal care and higher levels of maternal overprotection toward their children (e.g., Chang et al 2018). These findings are in contrast with those found among their Western counterparts (e.g., Ventola et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There are nine items for inattention (item 1–9) and nine items for hyperactivity/impulsivity (item 10-18) of the core symptoms of ADHD and eight items for the ODD symptoms according to the DSM-IV symptom criteria for ADHD and ODD ( 77 ). The psychometric properties of Chinese SNAP-IV Parent ( 22 ) and Teacher Form ( 21 ) have been established in Taiwan, and the scales have been frequently used to assess ADHD and ODD symptoms in clinical and research settings [e.g., ( 32 , 73 76 )].…”
Section: Methodsmentioning
confidence: 99%
“…Participants' parents and teachers completed questionnaires assessing the core symptoms of ADHD and related symptoms such as oppositionality by using the Chinese version of the Conners' parent and teacher rating scales-revised: short form (CPRS-R:S/CTRS-R:S) (19,34) and the Chinese version of the Swanson, Nolan, and Pelham, version IV scale (SNAP-IV) reported by parents (22) and teachers (21). These scales have been widely used in the screening for ADHD or measuring the intervention/treatment effect in clinical, community, and research settings (6,19,32,(70)(71)(72)(73)(74)(75)(76). Given that symptoms of oppositional defiant disorder (ODD) are included in all these scales and ODD symptoms are highly associated with ADHD and easily observed by teachers and parents (77), we included ODD items in the analyses and further hypothesized that ODD symptoms reported by teachers can distinguish ADHD from non-ADHD.…”
Section: Sample and Proceduresmentioning
confidence: 99%